Kajian Risiko Kesehatan Pajanan Bahaya Kimia Benzene, Toluene, dan Xylene pada Pekerja Laboratorium Lubricant PT X - Pratama, Muhammad Reyhan Ahadin; Tejamaya, Mila (UI Scholars Hub, 2025)
Lubricant laboratory pose various occupational safety and health hazards to their workers. Exposure to chemical hazards can occur through multiple routes and can lead to both acute and chronic health risks for laboratory workers. This study aims to analyze the health risks associated with exposure to benzene, toluene, and xylene (BTX) among lubricant laboratory workers at PT X. The study was conducted from February to June 2024 using a descriptive analytical research design with the chemical health risk assessment method from the Department of Safety and Health Malaysia (DOSH) 2018. Data collection techniques were employed quantitatively through personal exposure measurements for inhalation exposure and qualitatively for dermal exposure. The study results indicated a high risk level for benzene exposure and a low risk level for toluene and xylene additive exposure via inhalation. Meanwhile, a high-risk level was found for benzene exposure and a moderate risk level for toluene and xylene exposure via dermal exposure. The highest average exposure levels for benzene, toluene, and xylene were observed in the Sampling Team. Based on the study findings, appropriate control measures are necessary, such as providing appropriate Personal Protective Equipment (PPE), maintaining ventilation systems, and monitoring benzene, toluene, and xylene (BTX) exposure during routine and non-routine tasks. Keywords: lubricant laboratory, health risk assessment, BTX.